PENGARUH TOTAL ASSETS TURNOVER, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA PT NIPPON INDOSARI CORPINDO TBK PERIODE 2013-2022 - Dhea Dwi Octavia; Janudin (Journal of Research and Publication Innovation, 2024)
The objective of this research is to determine the influence of Total Asset Turnover, Current Ratio, and Debt to Equity Ratio on Net Profit Margin at PT Nippon Indosari Corpindo Tbk, both partially and simultaneously. The method used is the Quantitative Method, with the sample consisting of the financial summary, financial position report, and profit and loss statement of PT Nippon Indosari Corpindo Tbk for the period 2013-2022. Data analysis includes descriptive statistical tests, classical assumption tests, simple regression analysis, multiple regression analysis, hypothesis testing, autocorrelation tests, and determination coefficient tests. The partial test results show that Total Asset Turnover has a positive and significant effect on Net Profit Margin with a significance value of 0,013 < 0,05 and a t_count value of 3,508 > t_table 2,306. The Current Ratio has a negative and insignificant effect on Net Profit Margin with a significance value of 0,749 > 0,05 and a t_count value of -0,335 < t_table 2,306. The Debt to Equity Ratio has a positive and insignificant effect on Net Profit Margin with a significance value of 0,106 > 0,05 and a t_count value of 1,902 < t_table 2,306. Simultaneously, Total Asset Turnover, Current Ratio, and Debt to Equity Ratio have a positive and significant effect on Net Profit Margin with a significance value of 0,007 < 0,05 and an F_count value of 11,272 > F_table 4,530. The Determination Coefficient test results show an Adjusted R Square of 0,774, meaning that together, the influence of Total Asset Turnover, Current Ratio, and Debt to Equity Ratio on Net Profit Margin contributes 77,4%. Meanwhile, 22,6% is influenced by other variables not analyzed in this research.